2021
DOI: 10.1155/2021/6617270
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Existence of Ribosomal Protein L5 Gene in Syrian Strain of Leishmania tropica Genome: Sequencing It and Evaluating Its Immune Response as DNA Vaccine

Abstract: Cutaneous leishmaniasis in Syria is caused mainly by Leishmania tropica. It represents a serious health problem, which has aggravated further after the civil war in the country. Until now, there are no effective protective strategies, safe therapy, or efficacious vaccine to protect from this infection. DNA vaccines represent a promising approach for achieving protection against leishmaniasis. The L5 ribosomal protein plays fundamental roles in the assembly process of the ribosome subunits, so this study has ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Nevertheless, our results were in line with a few previous reports. In a study by Maarouf et al, the cell-mediated immunity caused by the DNA vaccine encoding Ribosomal protein L5 was Th1 type, which controlled the progression of L. tropica infection for up to 6 weeks in BALB/c mice (45). Furthermore, Rostamian et al demonstrated that vaccination with recombinant L. tropica stress-inducible protein-1 (LtSTI1) plus monophosphoryl lipid A (MPL), despite the low induction of immune responses (IFN-g and IL-10), significantly reduced parasite load in BALB/c mice lymph nodes up to week 16 th post-challenge (46).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results were in line with a few previous reports. In a study by Maarouf et al, the cell-mediated immunity caused by the DNA vaccine encoding Ribosomal protein L5 was Th1 type, which controlled the progression of L. tropica infection for up to 6 weeks in BALB/c mice (45). Furthermore, Rostamian et al demonstrated that vaccination with recombinant L. tropica stress-inducible protein-1 (LtSTI1) plus monophosphoryl lipid A (MPL), despite the low induction of immune responses (IFN-g and IL-10), significantly reduced parasite load in BALB/c mice lymph nodes up to week 16 th post-challenge (46).…”
Section: Discussionmentioning
confidence: 99%
“…It showed higher delayed type hypersensitivity (DTH) response and IFN-γ production [256]. L. tropica has also been used to construct DNA vaccine recently based on its ribosomal L5 gene, which exhibited up-regulated Th1 response following leishmanial infection [257].…”
Section: Killed Parasite Vaccinesmentioning
confidence: 99%